Modern method of construction: An experience from UK construction industry - Mohd Nawi, Mohd Nasrun; Abdul Nifa, Faizatul Akmar; Mohamad Kamar, Kamarul Anuar; Amphawan, Angela; Azman, Mohamed Nor Azhari (INSInet Publications, 2014)
Industrialised Building Systems (IBS) is commonly used interchangeably with other terms such as offsite construction, prefabrication, offsite manufacturing, modern method of construction (MMC), industrialised building and industrialised construction. However, the term modern method of construction (MMC) is used to collectively describe both offsite-based construction technologies and innovative onsite technologies in the United Kingdom. It is evident that there exist a wide range of contextual issues which stems from the definition of these terminologies.Nonetheless, no previous research has explored the relationship between these terminologies. This paper highlights the contrasting concepts of IBS and MMC, and concludes that ill-defining the MMC-IBS terms leads to misunderstanding, uncertainty and prejudice of the IBS concept and its benefits, which will be detrimental to efforts promoting the use of IBS in the construction industry